Estimating a sum

From Polymath Wiki
Jump to: navigation, search

For any [math]\sigma, t\gt0[/math] and natural number [math]N[/math], introduce the sum

[math]S_{\sigma,t}(N) := \sum_{n=1}^N \frac{1}{n^{\sigma + \frac{t}{4} \log\frac{N^2}{n}}}.[/math]

This sum appears a number of times in the Polymath15 project, and it is therefore of interest to estimate it.

Lemma 1 Let [math]\sigma,t\gt0[/math] and [math]N \geq N_0 \geq 1[/math]. Then

[math] \sum_{n=1}^{N_0} \frac{1}{n^{\sigma + \frac{t}{4} \log\frac{N^2}{n}}} \leq S_{\sigma,t}(N) \leq \sum_{n=1}^{N_0} \frac{1}{n^{\sigma + \frac{t}{4} \log\frac{N^2}{n}}} + \max( N_0^{1-\sigma - \frac{t}{4} \log \frac{N^2}{N_0}}, N^{1-\sigma - \frac{t}{4} \log N} ) \log \frac{N}{N_0}. [/math]

Proof The left-hand inequality is obvious. To prove the right-hand inequality, observe (from writing the summand as [math]\frac{\exp( \frac{t}{4} (\log N - \log n)^2}{n^\sigma \exp(\frac{t}{4} \log^2 N)}[/math]) that the summand is decreasing for [math]1 \leq n \leq N[/math], hence by the integral test one has

[math]S_{\sigma,t}(N) \leq \sum_{n=1}^{N_0} \frac{1}{n^{\sigma + \frac{t}{4} \log\frac{N^2}{n}}} + \int_{N_0}^N \frac{1}{a^{\sigma + \frac{t}{4} \log \frac{N^2}{a}}}\ da.[/math]

Making the change of variables [math]a = e^u[/math], the right-hand side becomes

[math]\sum_{n=1}^{N_0} \frac{1}{n^{\sigma + \frac{t}{4} \log\frac{N^2}{n}}} + \int_{\log N_0}^{\log N} \exp( (1-\sigma) u + \frac{t}{4} (u^2 - 2u \log N) )\ du.[/math]

The expression [math](1-\sigma) u + \frac{t}{4} (u^2 - 2u \log N)[/math] is convex in [math]u[/math], and is thus bounded by the maximum of its values at the endpoints [math]u = \log N_0, \log N[/math]; thus

[math]\exp( (1-\sigma) u + \frac{t}{4} (u^2 - 2u \log N) ) \leq \max( N_0^{1-\sigma - \frac{t}{4} \log \frac{N^2}{N_0}}, N^{1-\sigma - \frac{t}{4} \log N} ).[/math]

The claim follows. [math]\Box[/math]

Thus for instance if [math]\sigma = 0.7[/math], [math]t = 0.4[/math], and [math]N \geq N_0 = 2000[/math], one has

[math]S_{0.7, 0.4}(N) \leq \sum_{n=1}^{2000} \frac{1}{n^{0.7 + 0.1 \log \frac{N^2}{n}}} + \max( 2000^{0.3 - 0.1 \log \frac{N^2}{2000}}, N^{0.3 - 0.1 \log N}) \log \frac{N}{2000}. [/math]

One can compute numerically that the second term on the RHS is at most 0.0087, thus

[math]S_{0.7, 0.4}(N) \leq \sum_{n=1}^{2000} \frac{1}{n^{0.7 + 0.1 \log \frac{N^2}{n}}} + 0.0087[/math]

for all [math]N \geq 2000[/math]. In particular

[math]S_{0.7, 0.4}(N) \leq S_{0.7, 0.4}(2000) + 0.0087 \leq 1.706.[/math]

Similarly one has

[math]S_{0.3, 0.4}(N) \leq \sum_{n=1}^{2000} \frac{1}{n^{0.3 + 0.1 \log \frac{N^2}{n}}} + \max( 2000^{0.7 - 0.1 \log \frac{N^2}{2000}}, N^{0.7 - 0.1 \log N}) \log \frac{N}{2000}.[/math]

The second term can be shown to be at most [math]0.253[/math], thus

[math]S_{0.3, 0.4}(N) \leq S_{0.3, 0.4}(2000) + 0.253 \leq 3.469[/math]

for all [math]N \geq 2000[/math].

Evaluating many sums

Let [math]N[/math] be a natural number. For any complex numbers [math]z,w[/math], we define the quantity

[math]F_N(z,w) := \sum_{n=1}^N n^{-z + w \log n}.[/math]

In particular, the function [math]f_t(x+iy)[/math] in the writeup has the form

[math]f_t(x+iy) = F_N( \frac{1+y-ix}{2} + \frac{t}{2} \alpha(\frac{1+y-ix}{2}), \frac{t}{4} ) + \gamma \overline{F_N( \frac{1-y-ix}{2} + \frac{t}{2} \alpha(\frac{1-y-ix}{2}), \frac{t}{4} )}[/math]

It is thus of interest to efficiently evaluate [math]F_N(z,w)[/math] for multiple different values of [math]z,w[/math]. We will be particularly interested in the regime where [math]w=O(1)[/math] and [math]z = z_0 + \zeta[/math] for some [math]\zeta = O(1)[/math] and some fixed [math]z_0[/math] (e.g. [math]z_0 = \frac{1-iX}{2}[/math], thus

[math]F_N(z_0+\zeta, w) = \sum_{n=1}^N n^{-z_0} n^{-\zeta + w \log n}.[/math]

If one were to naively evaluate [math]F_N(-\frac{iX}{2}+\zeta, w)[/math] at [math]M[/math] different values of [math](z,w)[/math], this would require about [math]O(NM)[/math] operations. We now seek to use fewer operations to perform these evaluations, at the cost of some accuracy.

We can partition the interval [math]\{1,\dots,N\}[/math] into an initial segment [math]\{1,\dots,N_0\}[/math] and about [math]O(N/H)[/math] segments of the form [math]\{ N_i - H/2, \dots, N_i + H/2\}[/math] for various [math]N_i[/math]. This lets us split

[math]F_N(z_0+\zeta, w) = F_{N_0}(-\frac{iX}{2}+\zeta, w) + \sum_i \sum_{-H/2 \leq h \leq H/2} (N_i + h)^{-z_0} \exp( - \zeta \log(N_i+h) + w \log^2(N_i+h) ).[/math]

Writing [math]\log(N_i + h) = \log(N_i) + \varepsilon_{i,h}[/math], where [math]\varepsilon_{i,h} := \log(1 + \frac{h}{N_i})[/math], we thus have

[math]F_N(z_0+\zeta, w) = F_{N_0}(z_0+\zeta, w) + \sum_i \sum_{-H/2 \leq h \leq H/2} (N_i + h)^{-z_0} \exp( A_i(\zeta,w) + B_i(\zeta,w) \varepsilon_{i,h} + w \varepsilon_{i,h}^2 )[/math]


[math] A_i(\zeta,w) := - \zeta \log(N_i) + w \log^2(N_i)[/math]


[math] B_i(\zeta,w) := - \zeta + 2 w \log N_i.[/math]

From Taylor's theorem with remainder, we have

[math] \exp( a ) = \sum_{j=0}^T \frac{a^j}{j!} + O_{\leq}( \frac{|a|^{T+1}}{(T+1)!} \exp(|a|) )[/math]

and hence

[math]F_N(z_0+\zeta, w) = F_{N_0}(z_0+\zeta, w) + \sum_i \sum_{-H/2 \leq h \leq H/2} (N_i + h)^{-z_0} \exp( A_i(\zeta,w) ) \sum_{j=0}^T \frac{1}{j!} (B_i(\zeta,w) \varepsilon_{i,h} + w \varepsilon_{i,h}^2)^j + O_{\leq}( E )[/math]

where [math]E[/math] is the error term

[math] \sum_i \sum_{-H/2 \leq h \leq H/2} (n_0+h)^{-\mathrm{Re}(z_0)} \exp( \mathrm{Re} A_i(\zeta,w) ) \frac{|B_i(\zeta,w) \varepsilon_{i,h} + w \varepsilon_{i,h}^2|^{T+1}}{(T+1)!} \exp( |B_i(\zeta,w) \varepsilon_{i,h} + w \varepsilon_{i,h}^2| ).[/math]

By binomial expansion, we then have

[math]F_N(z_0+\zeta, w) = F_{N_0}(z_0+\zeta, w) + \sum_i \sum_{-H/2 \leq h \leq H/2} (N_i + h)^{-z_0} \exp( A_i(\zeta,w) ) \sum_{j_1,j_2 \geq 0: j_1+j_2 \leq T} \frac{1}{j_1! j_2!} (B_i(\zeta,w) \varepsilon_{i,h})^{j_1} (w \varepsilon_{i,h}^2)^{j_2} + O_{\leq}( E )[/math]

which we can rearrange as

[math]F_N(z_0+\zeta, w) = F_{N_0}(z_0+\zeta, w) + \sum_i \sum_{j=0}^{2T} \beta_{i,j,h} \sigma_{i,j}(\zeta,w)+ O_{\leq}( E )[/math]


[math] \beta_{i,j,h} := \sum_{-H/2 \leq h \leq H/2} (N_i + h)^{-z_0} \varepsilon_{i,h}^j[/math]


[math]\sigma_{i,j}(\zeta,w) := \sum_{j_1,j_2 \geq 0: j_1+2j_2 = j; j_1+j_2 \leq T} \frac{1}{j_1! j_2!} B_i(\zeta,w)^{j_1} w^{j_2}.[/math]

The point is that it only requires [math]O( \frac{N}{H} T H )[/math] calculations to compute the [math]\beta_{i,j,h}[/math], and [math]O( \frac{N}{H} T M )[/math] calculations to compute the [math]\sigma_{i,j}(\zeta,w)[/math], so the total computation time is now

[math]O( N_0 M + \frac{N}{H} T H + \frac{N}{H} T M + \frac{N}{H} T M ) = O( NM ( \frac{N_0}{N} + \frac{T}{M} + \frac{T}{H} ) )[/math]

which can be a significant speedup over [math]O(NM)[/math] when [math]N_0 \ll N[/math], [math]T \ll M[/math], and [math]T \ll H[/math].

Now we control the error term [math]E[/math]. From the concavity of the logarithm we have

[math]|\varepsilon_{i,h}| \leq |\varepsilon_{i,-H/2}| = \log \frac{N_i}{N_i-H/2} \leq \log(1 + \frac{H}{2N_0})[/math]


[math] |B_i(\zeta,w)| \leq |\zeta| + 2 |w| \log N[/math]

and hence

[math] E \leq \frac{\delta^{T+1}}{(T+1)!} \exp( \delta) \sum_i \exp( \mathrm{Re} A_i(\zeta,w) ) \sum_{-H/2 \leq h \leq H/2} (N_i+h)^{-\mathrm{Re} z_0} [/math]


[math] \delta := (|\zeta| + 2 |w| \log N) \log(1+\frac{H}{2N_0}) + |w| \log^2(1+\frac{H}{2N_0}).[/math]

Euler2 mollifier in the toy model

The toy version of preventing [math]H_t(x+iy)[/math] from vanishing is that of establishing the inequality

[math] |\sum_{n=1}^N \frac{1}{n^{\frac{1+y-ix}{2}+\frac{t}{4} \log \frac{N^2}{n} - \frac{\pi i t}{8}}}| \gt N^{-y} |\sum_{n=1}^N \frac{1}{n^{\frac{1-y-ix}{2}+\frac{t}{4} \log \frac{N^2}{n} - \frac{\pi i t}{8}}}|.[/math]

Direct application of the triangle inequality lets us do this if [math]S \lt 2[/math], where S is the sum

[math] S := \sum_{n=1}^N \frac{1}{n^{\frac{1+y}{2}+\frac{t}{4} \log \frac{N^2}{n}}} + \frac{N^{-y}}{n^{\frac{1-y}{2}+\frac{t}{4} \log \frac{N^2}{n}}}.[/math]

One can estimate S using the estimate in the first section of this web page.

Now we use a Euler2 mollifier. The lemma here is

Lemma Let [math]a_1,\dots,a_N[/math] be complex numbers, and let [math]b_2[/math] be a number such that whenever [math]1 \leq n \leq N[/math] is even, [math]b_n a_{n/2}[/math] lies on the line segment [math]\{ \theta a_n: 0 \leq \theta \leq 1\}[/math] connecting 0 with [math]a_n[/math]. Then we have the lower bound

[math] |1-b_2| |\sum_{n=1}^N a_n| \geq 2 |a_1| - (1-|b_2|) \sum_{n=1}^N |a_n| - 2 |b_2| \sum_{N/2 \lt n \leq N} |a_n|[/math]

and the upper bound

[math] |1-b_2| |\sum_{n=1}^N a_n| \leq (1-|b_2|) \sum_{n=1}^N |a_n| + 2 |b_2| \sum_{N/2 \lt n \leq N} |a_n|.[/math]

Proof The left-hand side can be written as

[math] |\sum_{n=1}^{2N} (1_{n \leq N} a_n - 1_{2|n} a_{n/2} b_2)|.[/math]

By the triangle inequality, this is bounded above by

[math] \sum_{n=1}^{2N} |1_{n \leq N} a_n - 1_{2|n} a_{n/2} b_2|[/math]

and below by

[math] 2 |a_1| - \sum_{n=1}^{2N} |1_{n \leq N} a_n - 1_{2|n} a_{n/2} b_2|.[/math]

We have

[math] \sum_{n=1}^{2N} |1_{n \leq N} a_n - 1_{2|n} a_{n/2} b_2| = \sum_{n=1}^N |a_n| - 1_{2|n} |a_{n/2}| |b_2| + \sum_{n=N+1}^{2N} 1_{2|n} |a_{n/2}| |b_2|[/math]

which we can rearrange as

[math] (1 - |b_2|) \sum_{n=1}^N |a_n| + 2 |b_2| \sum_{N/2 \lt n \leq N} |a_n|[/math]

and the claim follows.

We apply this lemma with [math]a_n = \frac{1}{n^{\frac{1 \pm y-ix}{2}+\frac{t}{4} \log \frac{N^2}{n} - \frac{\pi i t}{8}}}[/math] and [math]b_2 = \frac{1}{2^{\frac{1+y-ix}{2}+\frac{t}{4} \log \frac{N^2}{2} - \frac{\pi i t}{8}}}[/math]. The hypotheses of the lemma are easily verified, and we conclude that

[math] |1-b_2| |\sum_{n=1}^N \frac{1}{n^{\frac{1+y-ix}{2}+\frac{t}{4} \log \frac{N^2}{n} - \frac{\pi i t}{8}}}| \geq 2 - (1-|b_2|) \sum_{n=1}^N \frac{1}{n^{\frac{1+y}{2}+\frac{t}{4} \log \frac{N^2}{n}}} - 2 |b_2| \sum_{N/2 \lt n \leq N} \frac{1}{n^{\frac{1+y}{2}+\frac{t}{4} \log \frac{N^2}{n}}} [/math]


[math] |1-b_2| |\sum_{n=1}^N \frac{1}{n^{\frac{1-y-ix}{2}+\frac{t}{4} \log \frac{N^2}{n} - \frac{\pi i t}{8}}}| \leq (1-|b_2|) \sum_{n=1}^N \frac{1}{n^{\frac{1-y}{2}+\frac{t}{4} \log \frac{N^2}{n}}} + 2 |b_2| \sum_{N/2 \lt n \leq N} \frac{1}{n^{\frac{1-y}{2}+\frac{t}{4} \log \frac{N^2}{n}}}.[/math]

This leads to a modified criterion

[math] (1-|b_2|) S + 2 |b_2| \sum_{N/2 \lt n \leq N} \frac{1}{n^{\frac{1+y}{2}+\frac{t}{4} \log \frac{N^2}{n}}} + \frac{N^{-y}}{n^{\frac{1-y}{2}+\frac{t}{4} \log \frac{N^2}{n}}}) \lt 2.[/math]

We gain a factor of [math](1 - |b_2|)[/math] on the main term, but pick up an additional tail term summing over [math]N/2 \lt n \leq N[/math]. This tail term should be small for N large. The summand is monotone decreasing in N so we can majorise it by N/2 times the value at N/2, thus we obtain the simplified criterion

[math] (1 - |b_2|) S + N |b_2| \frac{1 + 2^{-y}}{(N/2)^{\frac{1+y}{2}+\frac{t}{4} \log(2N)}} \lt 2. [/math]